Material Selection Methodology for a Go-kart Chassis using FEA and Weighted Decision Matrices - Sanjeet Ramteke, Vaishnavi Nambiar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Performance enhancement in automobile parts is usually focussed on design optimization, but a periodic investigation into the material used can provide significant increments as well. This ideology is explored deeply in this paper as the material selection process of a go-kart chassis is demonstrated in the form of load calculations, property comparisons, and finite element analysis. The philosophy behind setting priorities in terms of mechanical properties and finite element analys is results is also discussed. The results are compared using a weighted decision matrix to ensure a balanced decision. This method of comparison can be divided into 3 steps where first, the properties are given weightage, followed by scoring and calculating a cumulative score for each material in correspondence with the criteria considered. These scores were then used to compare all the materials. The material selected based on the result improved the performance of the chassis in terms of safety and performance in a student competition